2015
DOI: 10.1002/phar.1643
|View full text |Cite|
|
Sign up to set email alerts
|

Immune Checkpoint Inhibitors: New Insights and Current Place in Cancer Therapy

Abstract: The treatment of cancer has largely relied on killing tumor cells with nonspecific cytotoxic therapies and radiotherapy. This approach, however, has limitations including severe systemic toxicities, bystander effects on normal cells, recurrence of drug-resistant tumor cells, and the inability to target micrometastases or subclinical disease. An increased understanding of the critical role of the immune system in cancer development and progression has led to new treatment strategies using various immunotherapie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
178
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 201 publications
(185 citation statements)
references
References 49 publications
1
178
0
3
Order By: Relevance
“…PD-1 blockade can reverse tumor-induced T cell dysfunction and lead to heightened antitumor immunity and cancer regression (La-Beck et al, 2015). We thus wanted to determine whether PD-1 blockade might rescue loss of mitochondrial function in tumorinfiltrating T cells.…”
Section: Loss Of T Cell Oxidative Metabolism In Cancer Is Largely Indmentioning
confidence: 99%
See 2 more Smart Citations
“…PD-1 blockade can reverse tumor-induced T cell dysfunction and lead to heightened antitumor immunity and cancer regression (La-Beck et al, 2015). We thus wanted to determine whether PD-1 blockade might rescue loss of mitochondrial function in tumorinfiltrating T cells.…”
Section: Loss Of T Cell Oxidative Metabolism In Cancer Is Largely Indmentioning
confidence: 99%
“…Recent advances in cancer immunotherapy have revealed that the T cell response to cancer can be reinvigorated in a variety of ways, resulting in durable and effective benefit in a wide array of cancer types (La-Beck et al, 2015;Mahoney et al, 2015;Ribas, 2015). These include engineering chimeric antigen receptors redirect T cells to tumors, personalized antigen vaccines to persistent neoepitopes, and, probably most prominently, antibodymediated blockade of co-inhibitory "checkpoint" molecules, like programmed death-1 (PD-1), cytotoxic T lymphocyte antigen 4 (CTLA-4), lymphocyte activation gene 3 (LAG-3), T cell immunoglobulin and mucin-containing gene 3 (Tim-3), among others (LaBeck et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sie blockieren kostimulatorische Signale der Immunaktivierung und führen zu einer T-Zell-Anergie und Immunsuppression. In der Tumortherapie bietet die Blockade dieses Signalwegs (Immuncheckpointinhibition) mit dem Ziel der Steigerung der T-Zell-vermittelten Immunantwort gegen Tumorzellen neue Behandlungsoptionen für eine Reihe von Krebsarten wie das metastasierte Melanom, nichtkleinzellige Lungenkarzinom und das Nierenzellkarzinom [21].…”
Section: Immuncheckpointinhibitoren Und Nebenwirkungenunclassified
“…[12][13][14][15][16][17] A major limitation of the approach is its unspecific nature of T cell targeting, resulting in severe side effects. [18][19][20] Strategies allowing for a more directed and specific therapeutic use of T cells may have advantages in terms of specificity and efficacy. …”
mentioning
confidence: 99%